Дослідження технологій доступу до реляційних баз даних - Рамазанов, Р. Ш. (ХНУРЕ, 2023)
This work is devoted to the study and comparison of various methods of accessing relational databases on the .NET platform. An analysis of the e-commerce domain was carried out and a database structure was developed for conducting experiments. Three different repositories have been developed, one for each access method under investigation. A pilot study was conducted, during which the effectiveness of each implementation was evaluated. The obtained results made it possible to formulate recommendations for the practical use of the studied access technologies.